Asymptotic integration of a singularly perturbed quasilinear cauchy problem in a banach space - Plotkin, Ya. D.; Turbin, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We investigate the asymptotic behavior of a solution of a singularly perturbed quasilinear abstract differential equation in a Banach space.